THE EFFECTS OF NATIVE SPEAKER RECORDING ON STUDENTS’ LISTENING ABILITY AT SMAN 3 WANGI-WANGI WAKATOBI REGENCY SOUTHEAST SULAWESI - Muh. Nurul Abdullah (Teaching English as a Foreign Language Overseas Journal, 2020)
The purpose of this research is to know the effect of Native Speaker on students' listening. The results of this study are expected to be useful for students to enrich the listening ability, and can help teachers to be more creative. The research method applied is pre-experimental method by using a pre-test, treatment, and post-test. The subject of this research is XI/IPS 1 and XI/IPS 2 at SMAN 3 Wangi-wangi. This research applied total sampling technique, with a total sample of 20 students. The result of data analysis shown that there was a significant effect of students’ listening by using audiovisual native speaker as a media in the learning process. It can be seen from the value of the t-test is 4.01 higher than t-table is 2.027. Obtaining the student scores indicate that usage of audiovisual Native Speaker can effect on students' listening mastery in VIII/IPS 1 and XI/IPS 2 SMAN 3 Wangi-wangi.